Easy PC - محليس, دانيه; ابو شرخ, حلا; دوفش, عبد الرحمن (جامعة بوليتكنك فلسطين - تكنولوجيا المعلومات, 2023)
Due to the rapid development in the field of technology and its entry into all areas of life; To help complete the tasks in the shortest time and with the least possible effort, we have developed an e-commerce application that connects the seller and the buyer easily and offers many advantages that make it easier for both parties to deal in the field of trading and trading everything related to modern electronic devices and accessories. The importance of the site lies in the fact that it will be a point of intersection for everyone who wants to buy, sell, or display computer parts, so people will be aware of a suitable place to display used items that they will not use again, and the buyer who wants to buy a used item at a certain price will have the opportunity to search optimally in the place suitable, as it targets all population groups that deal with modern technology of all kinds. The idea of the application: The application allows all groups to access everything related to modern computer devices, so that it gives an opportunity for the seller to promote his products, and for the buyer to find his needs, and thus each of the parties gets what he wants, so that the application allows the user to deal with other users on the application in a capacity The user is a seller and also in his capacity as a buyer, so that he can display his products and sell them by registering them on the publications page that displays the products available for sale and deals as a buyer, as he displays the same page to find what he is looking for and communicates with the seller and purchases the specific product. When displaying a specific product on the publications page, the selling user registers the product in a special publication in which he talks about all the specifications and advantages of the product in a way that attracts the buyer, and he puts some of his personal information such as phone number, email, and address in addition to the original details of the product, so the buyer searches for the product he wants. He finds it on the publications page, then contacts the seller, they exchange information, and the deal is completed
تطبيق لعرض القطع الحاسوبية والربط بين التجار والمستخدمين لاجراء البيع والشراء من خلالهم.
no of pages 45, تكنولوجيا معلومات 3/2023
Keywords: الحاسوب - قطع